(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
A Fog Based authentication technique was developed by Awais et al. for vehicular ad hoc network. In their article, they introduced Fog based authentication protocol based on a password and smart card. They claimed that their technique is impervious to a variety of assaults, including offline password guessing attempt and insider attack. However, after reviewing their scheme, we found some flaws in it, such as insider attack, offline password guessing attack. In conclusion, we offer several recommendations to enhance the analysed scheme and address the identified weaknesses.